An investigation into the influence of an inset programme on teacher cognitions - Bell, David Ian (Rhodes University, Faculty of Education, Department of Education, 1995)
This study was based upon a concern about the quality of education in South Africa and a concern about the quality of NGO and other INSET interventions. Many organisations purport to address the issues of education, most of them doing so from the very comfortable position of the moral high ground (the position adopted where the political - correctness of the intervention outweighs the quality and impact) rather than from the position of having the capacity to deliver a quality service (a position from which they can effect genuine educational transformation toward quality education for all). With the rapid social, political and educational changes taking place at present, it is necessary for most organisations to assess their positions in respect of their ability to effect quality changes within the broad educational terrain. This study is an attempt to investigate the influence of one particular programme, that of the Centre for Cognitive Development, as it effects changes in teacher cognitions. It is argued that teachers are the catalysts for and agents of educational and social change and that these changes require the thinking and beliefs of individual teachers which inform their practices and behaviours, both personally and as professionals, to be addressed. These beliefs need to be critically reflected upon by the teachers themselves and through this process of reflection, teachers need to be empowered to take responsibility for the quality of teaching and learning. This concern was addressed by selecting a sample of teachers from within one such INSET intervention and through the use of a questionnaire, investigating whether teachers cognitions had changed, as a result of the INSET programme. It was hypothesised that changes in teacher cognitions would occur as a result of the INSET programme and that these cognitive or gestalt shifts could be categorised as Attributional shifts, Efficacy shifts, shifts in teachers perceived Locus of Control (Control Beliefs) and changes in general Pedagogic Beliefs. The statistical analysis of the data indicated varying degrees and trends of significant change. However, the complexity of the social context of teaching and the impact of this on teacher beliefs and cognitions, especially those of teachers who have been most affected (disempowered) by social and personal oppression, cannot be under-estimated and even minor shifts reflected in this investigation should be seen as positive changes none-the-less.
Keywords: Teachers -- In-service training -- South Africa; Teachers -- South Africa